5.27.9 Problems 801 to 900

Table 5.1183: Second order, Linear, non-homogeneous and constant coefficients

#

ODE

Mathematica

Maple

8065

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{2}+2 x +2 \]

8066

\[ {}y^{\prime \prime }+y^{\prime } = \frac {x -1}{x} \]

8068

\[ {}y^{\prime \prime }+9 y = -3 \cos \left (2 x \right ) \]

8167

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 5 \,{\mathrm e}^{3 t} \]

8168

\[ {}y^{\prime \prime }+y^{\prime }-6 y = t \]

8169

\[ {}y^{\prime \prime }-y = t^{2} \]

8173

\[ {}y^{\prime \prime }+3 y^{\prime }-5 y = 1 \]

8174

\[ {}y^{\prime \prime }+3 y^{\prime }-2 y = -6 \,{\mathrm e}^{-t +\pi } \]

8175

\[ {}y^{\prime \prime }+2 y^{\prime }-y = t \,{\mathrm e}^{-t} \]

8176

\[ {}y^{\prime \prime }-y^{\prime }+y = 3 \,{\mathrm e}^{-t} \]

8178

\[ {}y^{\prime \prime }+3 y^{\prime }+3 y = 2 \]

8179

\[ {}y^{\prime \prime }+y^{\prime }+2 y = t \]

8180

\[ {}y^{\prime \prime }-7 y^{\prime }+12 y = t \,{\mathrm e}^{2 t} \]

8181

\[ {}i^{\prime \prime }+2 i^{\prime }+3 i = \left \{\begin {array}{cc} 30 & 0<t <2 \pi \\ 0 & 2 \pi \le t \le 5 \pi \\ 10 & 5 \pi <t <\infty \end {array}\right . \]

8329

\[ {}y^{\prime \prime }-4 y^{\prime } = 6 \,{\mathrm e}^{3 t}-3 \,{\mathrm e}^{-t} \]

8330

\[ {}y^{\prime \prime }+y = \sqrt {2}\, \sin \left (\sqrt {2}\, t \right ) \]

8331

\[ {}y^{\prime \prime }+9 y = {\mathrm e}^{t} \]

8339

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = t^{3} {\mathrm e}^{2 t} \]

8340

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = t \]

8341

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = t^{3} \]

8344

\[ {}y^{\prime \prime }-y = {\mathrm e}^{t} \cos \left (t \right ) \]

8345

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = t +1 \]

8351

\[ {}y^{\prime \prime }+4 y = \left \{\begin {array}{cc} 1 & 0\le t <1 \\ 0 & 1\le t \end {array}\right . \]

8352

\[ {}y^{\prime \prime }+4 y = \operatorname {Heaviside}\left (t -2 \pi \right ) \sin \left (t \right ) \]

8353

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = \operatorname {Heaviside}\left (t -1\right ) \]

8354

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} 0 & 0\le t <\pi \\ 1 & \pi \le t <2 \pi \\ 0 & 2 \pi \le t \end {array}\right . \]

8355

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = 1-\operatorname {Heaviside}\left (t -2\right )-\operatorname {Heaviside}\left (t -4\right )+\operatorname {Heaviside}\left (t -6\right ) \]

8358

\[ {}y^{\prime \prime }+9 y = \cos \left (3 t \right ) \]

8359

\[ {}y^{\prime \prime }+y = \sin \left (t \right ) \]

8360

\[ {}y^{\prime \prime }+16 y = \left \{\begin {array}{cc} \cos \left (4 t \right ) & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right . \]

8361

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} 1 & 0\le t <\frac {\pi }{2} \\ \sin \left (t \right ) & \frac {\pi }{2}\le t \end {array}\right . \]

8364

\[ {}y^{\prime \prime }+y = \sin \left (t \right )+t \sin \left (t \right ) \]

8367

\[ {}y^{\prime \prime }+y = \delta \left (t -2 \pi \right ) \]

8368

\[ {}y^{\prime \prime }+16 y = \delta \left (t -2 \pi \right ) \]

8369

\[ {}y^{\prime \prime }+y = \delta \left (t -\frac {\pi }{2}\right )+\delta \left (t -\frac {3 \pi }{2}\right ) \]

8370

\[ {}y^{\prime \prime }+y = \delta \left (t -2 \pi \right )+\delta \left (t -4 \pi \right ) \]

8371

\[ {}y^{\prime \prime }+2 y^{\prime } = \delta \left (t -1\right ) \]

8372

\[ {}y^{\prime \prime }-2 y^{\prime } = 1+\delta \left (t -2\right ) \]

8373

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = \delta \left (t -2 \pi \right ) \]

8374

\[ {}y^{\prime \prime }+2 y^{\prime }+y = \delta \left (t -1\right ) \]

8375

\[ {}y^{\prime \prime }+4 y^{\prime }+13 y = \delta \left (t -\pi \right )+\delta \left (t -3 \pi \right ) \]

8376

\[ {}y^{\prime \prime }-7 y^{\prime }+6 y = {\mathrm e}^{t}+\delta \left (t -2\right )+\delta \left (t -4\right ) \]

8378

\[ {}y^{\prime \prime }+2 y^{\prime }+10 y = \delta \left (t \right ) \]

8529

\[ {}y^{\prime \prime }+y = -\cos \left (x \right ) \]

8530

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{x} \]

8531

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 12 x^{2} \]

8532

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = x^{2}+2 x +1 \]

8705

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 5 \,{\mathrm e}^{2 x} \]

8706

\[ {}y^{\prime \prime }+16 y = 4 \cos \left (x \right ) \]

8707

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 9 x^{2}+4 \]

8708

\[ {}y^{\prime \prime }+y = \tan \left (x \right )^{2} \]

8754

\[ {}y^{\prime \prime }+y^{\prime }+4 y = 1 \]

8755

\[ {}y^{\prime \prime }+y^{\prime }+4 y = \sin \left (x \right ) \]

8767

\[ {}y^{\prime \prime } = 1 \]

8768

\[ {}y^{\prime \prime } = f \left (t \right ) \]

8769

\[ {}y^{\prime \prime } = k \]

8772

\[ {}y^{\prime \prime } = 4 \sin \left (x \right )-4 \]

8795

\[ {}z^{\prime \prime }+3 z^{\prime }+2 z = 24 \,{\mathrm e}^{-3 t}-24 \,{\mathrm e}^{-4 t} \]

8861

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8862

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8863

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8864

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8865

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8866

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8867

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8868

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8869

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

8870

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

8871

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

8960

\[ {}y^{\prime \prime }+20 y^{\prime }+500 y = 100000 \cos \left (100 x \right ) \]

8977

\[ {}y^{\prime \prime }+2 y^{\prime }-24 y = 16-\left (x +2\right ) {\mathrm e}^{4 x} \]

8978

\[ {}y^{\prime \prime }+3 y^{\prime }-4 y = 6 \,{\mathrm e}^{2 t -2} \]

9078

\[ {}y^{\prime \prime } = 1 \]

9079

\[ {}{y^{\prime \prime }}^{2} = 1 \]

9080

\[ {}y^{\prime \prime } = x \]

9081

\[ {}{y^{\prime \prime }}^{2} = x \]

9086

\[ {}y^{\prime \prime }+y^{\prime } = 1 \]

9089

\[ {}y^{\prime \prime }+y^{\prime } = x \]

9095

\[ {}y^{\prime \prime }+y^{\prime }+y = 1 \]

9096

\[ {}y^{\prime \prime }+y^{\prime }+y = x \]

9097

\[ {}y^{\prime \prime }+y^{\prime }+y = 1+x \]

9098

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{2}+x +1 \]

9099

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{3}+x^{2}+x +1 \]

9100

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

9101

\[ {}y^{\prime \prime }+y^{\prime }+y = \cos \left (x \right ) \]

9102

\[ {}y^{\prime \prime }+y^{\prime } = 1 \]

9103

\[ {}y^{\prime \prime }+y^{\prime } = x \]

9104

\[ {}y^{\prime \prime }+y^{\prime } = 1+x \]

9105

\[ {}y^{\prime \prime }+y^{\prime } = x^{2}+x +1 \]

9106

\[ {}y^{\prime \prime }+y^{\prime } = x^{3}+x^{2}+x +1 \]

9107

\[ {}y^{\prime \prime }+y^{\prime } = \sin \left (x \right ) \]

9108

\[ {}y^{\prime \prime }+y^{\prime } = \cos \left (x \right ) \]

9109

\[ {}y^{\prime \prime }+y = 1 \]

9110

\[ {}y^{\prime \prime }+y = x \]

9111

\[ {}y^{\prime \prime }+y = 1+x \]

9112

\[ {}y^{\prime \prime }+y = x^{2}+x +1 \]

9113

\[ {}y^{\prime \prime }+y = x^{3}+x^{2}+x +1 \]

9114

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

9115

\[ {}y^{\prime \prime }+y = \cos \left (x \right ) \]

11013

\[ {}y^{\prime \prime }+y-\sin \left (n x \right ) = 0 \]